In order of disappearance [videorecording (DVD)] - Skarsgård, Stellan; Hivju, Kristofer, 1978-; Hagen, Pål Sverre Valheim (Magnolia Home Entertainment, 2016)
The honorable citizen Nils plows snow in the wild winter mountains of Norway, but when his son is mistakenly murdered, Nils takes action, which ignites a war between the vegan gangster "the Count" and the Serbian mafia boss Papa.